Efektivitas Pelaksanaan Program Keluarga Harapan (PKH) Dalam Upaya Penanggulangan Kemiskinan Di Desa Lonuo Kecamatan Tilingkabila Kabupaten Bonebolango - Dewi Afriani Djabar; Fahrudin Zain Olilingo; Ivan Rahmat Santoso (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effectiveness of the implementation of the Family Hope Program (PKH) in poverty reduction efforts in Lonuo Village, Tilongkabila District, Bone Bolango Regency. To analyze the effectiveness of program implementation, this study used primary data in the form of a questionnaire containing questions about the implementation of PKH. A total of 50 beneficiaries were used as respondents in this study so as to obtain the effectiveness of program implementation by calculating the effectiveness ratio with three approaches, namely the resource approach, process approach, and target approach. Based on the results of the analysis, it is found that of the three approaches, namely the resource approach, process approach and target approach, all of them provide very effective effectiveness. The government must continue to monitor the PKH program so that the benefits felt by the community are in line with the program's objectives.